Fighting corruption is dangerous the story behind the headlines - Okonjo-Iweala, Ngozi (Cambridge The Mit Press, 2018)
In Fighting Corruption Is Dangerous, Ngozi Okonjo-Iweala has written a primer for those working to root out corruption and disrupt vested interests. Drawing on her experience as Nigeria's finance minister and that of her team, she describes dangers, pitfalls, and successes in fighting corruption. She provides practical lessons learned and tells how anti-corruption advocates need to equip themselves. Okonjo-Iweala details the numerous ways in which corruption can divert resources away from development, rewarding the unscrupulous and depriving poor people of services.
Includes bibliographical references (pages 163-173).
Keywords: Okonjo-Iweala, Ngozi